The Effect of Good Corporate Governance on Corporate Social Responsibility on Company Value With Profitability as an Intervening Variable (Empirical Study on Consumer Goods Sector Companies Listed on the Indonesia Stock Exchange for the 2019-2023 Period) - Risa Bonani Prastika; Rusdi Hidayat Nugroho; Budi Prabowo; Indah Respati Kusumasari (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
With profitability serving as a mediator, this research seeks to examine the impact of Good Corporate Governance and Corporate Social Responsibility on business value. Managerial ownership, institutional ownership, and independent commissioners are the proxies of good corporate governance. The GRI is what's known as "Corporate Social Responsibility" in the business world. Return on Assets (ROA) is a measure of profitability, while Price to Book worth (PBV) is a method for calculating a company's worth. The 23 consumer products businesses listed on the Indonesia Stock Exchange from 2019 to 2023 made up the population in this research. Utilizing inferential statistical analysis tools and a purposive sample procedure, this research quantifies its findings via statistical analysis. For the purpose of calculating each variable, data is retrieved utilizing documentation approaches by obtaining sustainability reports and annual reports from the Indonesia Stock Exchange's official website. This research found that good corporate governance has an effect on company value and profitability. Firm value is unaffected by corporate social responsibility, on the other hand. Firm value is influenced by profitability, which is an independent variable. Good corporate governance may increase a company's value, although profitability might mitigate this benefit. The impact of CSR on company value cannot be moderated by profitability as a mediator variable. This research has many limitations that make it unsuitable for use as a comprehensive reference for enterprises outside of the consumer products industry. It is recommended that future studies include firms from other sectors and include additional elements that contribute to the growth of company value.